Radio polarization properties for blazars - Fan, Jun Hui (2008)
We used data from the University of Michigan Radio Astronomy Observatory (UMRAO) at three different bands (4.8 GHz, 8 GHz, and 14.5 GHz) to calculate the radio spectral index and the averaged polarization in a sample of 92 flat spectrum radio quasars (FSRQs). We analyzed the relationship between the polarization and other physical parameters for these objects. The results show that: 1) the polarization and its variability at high radio frequencies are higher than those at lower frequencies, 2) the degree of linear polarization is correlated with the radio spectral index, suggesting that the synchrotron mechanism is responsible for the radio emission, 3) the polarization is correlated with the core-dominance parameter for those objects for which this parameter is known, which suggests that relativistic beaming could explain some polarization characteristics of FSRQs, and 4) the polarization and flux density variabilities are correlated. These results are similar to those found for RBLs in our previous work (Fan et al. 2006). However, the distributions in the averaged polarization and the spectral index in FSRQs are different from those in RBLs.